THE JADID MOVEMENT AND ITS HISTORICAL SIGNIFICANCE - Shaymuratova Marjona; Kholboboeva Khurshida (Ustozlar uchun, 2025)
The Jadid movement emerged in the late 19th and early 20th centuries as a reformist initiative among Muslim communities in Central Asia, particularly within the Russian Empire. Advocating for educational, cultural, and social renewal, Jadid intellectuals sought to modernize Islamic society by integrating contemporary scientific knowledge and secular subjects with traditional religious teachings. This movement played a pivotal role in shaping national consciousness, promoting literacy, and resisting colonial domination through peaceful reform rather than confrontation. The study of the Jadid movement reveals its deep historical significance as a catalyst for intellectual awakening, socio-political change, and the eventual formation of national identities in Central Asia.